HUBUNGAN FAKTOR-FAKTOR PRAEVENIRE KAMBUH ULANG /RELAPS TB PARU DI POLI PUSKESMAS SIDOMULYO TUAH MADANI KOTA PEKANBARU - Chairil; Carles; Draini, Osi (Journal of Hospital Administration and Management (JHAM), 2025)
Pulmonary tuberculosis (TB) is an infectious disease that remains a significant public health problem due to its ease of transmission and high risk of recurrence (relapse), especially among patients who do not undergo optimal treatment. Relapse of pulmonary TB can be influenced by various preventive (praevenire) factors, such as incomplete treatment, low income, irregular medication intake, and lack of family support.This study aims to determine the relationship between these praevenire factors and the incidence of pulmonary TB relapse at the Sidomulyo Tuah Madani Public Health Center in Pekanbaru City. The study was conducted from April to June using a quantitative approach with a cross-sectional design. A total of 82 respondents participated, and data analysis was performed using the chi-square test with continuity correction.The results showed that the majority of respondents were 54 years old (66%), unemployed (54%), had a high school education (51.22%), and were male (54%). There were significant associations between incomplete treatment (p=0.027), income below the minimum wage (p=0.047), and irregular medication intake (p=0.045) with the occurrence of pulmonary TB relapse. However, family support did not show a significant relationship (p=0.361).In conclusion, several praevenire factors are associated with pulmonary TB relapse. Therefore, continuous interventions are needed to improve patient awareness and social support to ensure optimal treatment and prevent recurrence.